2016
DOI: 10.3390/land5040035
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Species in Protected Areas and Community-Managed Lands in Arunachal Pradesh, Northeast India

Abstract: Protected areas (including areas that are nominally fully protected and those managed for multiple uses) encompass about a quarter of the total tropical forest estate. Despite growing interest in the relative value of community-managed lands and protected areas, knowledge about the biodiversity value that each sustains remains scarce in the biodiversity-rich tropics. We investigated the species occurrence of a suite of mammal and pheasant species across four protected areas and nearby community-managed lands i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…We also demonstrated a strong positive impact of strict PAs on larger and threatened mammals, which seems to be part of a broader trend of large-bodied species benefitting more from strict protection than smaller species (Drouilly et al, 2018;Kinnaird and O'brien, 2012;Rich et al, 2016;Velho et al, 2016). Interestingly, size seems to have even greater influence on the effect of strict protection than threat status in the mammal community studied.…”
Section: Biodiversity Patterns In Contrasting Levels Of Protectionmentioning
confidence: 57%
“…We also demonstrated a strong positive impact of strict PAs on larger and threatened mammals, which seems to be part of a broader trend of large-bodied species benefitting more from strict protection than smaller species (Drouilly et al, 2018;Kinnaird and O'brien, 2012;Rich et al, 2016;Velho et al, 2016). Interestingly, size seems to have even greater influence on the effect of strict protection than threat status in the mammal community studied.…”
Section: Biodiversity Patterns In Contrasting Levels Of Protectionmentioning
confidence: 57%
“…However, caution is required. Velho et al [12] found that, while many native species are present in the locally managed lands adjacent to three protected areas in Northeast India, the larger mammals were generally absent, being restricted to the protected areas. There is clearly a role for locally managed lands in protecting regional biodiversity, but they complement protected areas-they do not substitute for them.…”
mentioning
confidence: 99%
“…We identified and interviewed 37 experienced hunters (mean age: 54, range: 29-79) in the study area, with help from local colleagues who were born and raised there. We showed them photographs of mammals in the checklist and asked them to rank each species from À2 (large declines in abundance) to +2 (large increases in abundance), with a rank of zero indicating no change, following Velho et al (2016aVelho et al ( , 2016b. To avoid confusion between similar looking species in photographs, we considered all the three macaques species (Macaca spp.)…”
Section: Hunter Interviewsmentioning
confidence: 99%